Selection gains for the palm oil production from progenies of American oil palm with oil palm - Rui Alberto Gomes Junior; Alessandra Ferraiolo de Freitas; Raimundo Nonato Vieira da Cunha; Antônio José de Abreu Pina; Higo Otávio Brochado Campos; Ricardo Lopes (Pesquisa Agropecuária Brasileira, 2021)
Abstract The objective of this work was to estimate the genetic parameters, correlations, and selection gains for the oil production of interspecific hybrids progenies between American oil palm, of ‘Manicoré’ origin, and oil palm, of ‘La Mé’ origin. Thirty-nine progenies were evaluated from the sixth to the ninth year after planting, for the productivity of fresh fruit bunches (PROD_FFB), oil content in the bunch (OCB), and palm oil productivity (PROD_OP). The genetic parameters and gains from direct (GDS) and indirect (GIS) selection were estimated for PROD_OP. High values of heritability for the CVg/CVe ratio indicated favorable conditions for the selection. With the selection of 20% of the progenies (selection in both sexes), the following estimates were obtained: 11.15% GDS for PROD_OP, 9.1% GIS for OCB, and 8.1% GIS for PROD_FFB. The PROD_OP of the progenies was of 6,175, 6,057, and 5,995 kg ha-1 per year with GDS and GIS for OCB and PROD_FFB, respectively. The restricted selection of the LM2T male genitor offspring resulted in 5.1% estimated GSD and in a mean of 5,800 kg ha-1 per year for PROD_OP. Selection gains for PROD_OP can be achieved immediately through the selection restricted to oil palm male genitors, and, in the medium and long term, through the interspecific reciprocal recurrent selection between American oil palm and oil palm populations.